2012
DOI: 10.3329/dujps.v11i1.12481
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Studies of Some 4-(Substituted)-Ethanoylamino-3-Mercapto-5- (4-Substituted) Phenyl-1,2,4-Triazoles

Abstract: Triazoles and triazoles with different substituent groups are found to possess diverse application in the field of medicine and industry. A series of 4-(substituted) ethanoylamino-3-mercapto-5-(4-substituted) phenyl-1,2,4-triazoles were synthesized as novel antimicrobial agents starting from different 4-substituted benzoic acids. The chemical structures of these newly synthesized compounds were elucidated by IR, 1 H NMR, 13 C NMR, FAB + -mass spectral data and elemental analyses. The antimicrobial activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…One of the observed resonances is found to be at higher chemical shift region due to deshielding effect of neighbouring C=O moiety [23]. In the range of δ H 7.95-6.78 ppm, roofing effect due to para substituted phenyl group can be observed in T2 and T3 [24]. However, different pattern at δ H 8.02-7.52 ppm is observed due to presence of tri-substituted phenyl in T1.…”
Section: V(c-h) V(c=o) V(c=n)mentioning
confidence: 87%
“…One of the observed resonances is found to be at higher chemical shift region due to deshielding effect of neighbouring C=O moiety [23]. In the range of δ H 7.95-6.78 ppm, roofing effect due to para substituted phenyl group can be observed in T2 and T3 [24]. However, different pattern at δ H 8.02-7.52 ppm is observed due to presence of tri-substituted phenyl in T1.…”
Section: V(c-h) V(c=o) V(c=n)mentioning
confidence: 87%
“…Previous studies showed that 1,2,4-triazole derivatives are important group in the field of medicinal chemistry due to their diverse biological properties [23]. The biological activity of triazoles is highly dependent on the chemical side groups that may enhance their activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrazinolysis of compounds IIa-IIb gave the corresponding acetohydrazides (IIIa-IIIb) in good yields [30,32]. One mole of the compound IIa or IIb in ethanol was heated for 4-6 h with hydrazine hydrate (two moles).…”
Section: Mechanism Of the Pechmann Condensationmentioning
confidence: 99%
“…The reaction of the acid hydrazides (4-methyl/propyl-2-oxo-2H-benzopyran-7oxyacetic acid hydrazide) with CS 2 in ethanol containing KOH at room temperature has been presented in Figure 6. The corresponding potassium dithiocarbazate derivatives, IVa-IVb, are obtained [32].…”
Section: Mechanism Of the Pechmann Condensationmentioning
confidence: 99%